ANALISIS FAKTOR-FAKTOR PENYEBAB SLOW MOVING ITEM ALKOHOL DI PANTAI INDAH LAGOI - Nakila Wavita Bintani; Siti Mukharomah Pujirestuti; Putri Patrisia (JURNAL MATA PARIWISATA, 2025)
Slow moving products are items with very a slow turnover rate. These items move through inventory at such a slow pace that they typically remain in storage for extended periods. Slow moving inventory could happen from several factors such as pricing issues, lack of promotion, low demand, insufficient product innovation, and limited variety and choices, all of which contribute to the slow sales of these products. This slow-moving issue is also observed at Pantai Indah Lagoi, especially with alcoholic beverages stored in the food and beverage store which managed by purchasing Where less than a year only one product that released from the store that shows how high the slow moving at the Hotel is. The goal of the research is to know what is the factors that causing a slow moving to the alcohol product at Pantai Indah Lagoi. The method of this research is qualitative which to point all the caused and the factors of the slow-moving items at Pantai Indah Lagoi. The methods of this data collection was include observing the inventory data of alcoholic beverages in the Food and Beverage Store and conducting interviews with the Food and Beverage Service and Purchasing Departments. Based on the results of interview could take the summary that the factors which causing a slow moving for the alcohol product at this Hotel is there is not much of the demand for the alcohol drinks which cause the lack of the selling, lack of product innovation that caused of lacking unique features that attract customers at Pantai Indah Lagoi. insufficient promotion already being made which were not effectively implemented, and a limited selection of alcoholic beverage brands leading to a customer dissatisfaction with the available drink options.